From Blackbeard to Jack Sparrow—Who are today’s pirates and why do we care? The effect the legal definition of piracy has on the international shipping industry and maritime insurance coverage - Schumacher, Jamie (Journal of Law and Commerce, 2013)
<!–[if gte mso 9]> 96 800x600 <![endif]–> <!–[if gte mso 9]> Normal 0 false false false EN-US JA X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Cambria; –> <!–[endif] –> <!–StartFragment–> <!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 false false false EN-US JA X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; mso-pagination:widow-orphan; font-size:12.0pt; font-family:Cambria; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Cambria; mso-hansi-theme-font:minor-latin; –> <!–[endif] –> <!–StartFragment–> <!–EndFragment–> Today’s pirates may seem more like terrorists, and their effect can be felt on a variety of sectors within society, most notably international commerce. The shipping industry deals with the threat of pirate attacks on a regular basis. In order to prevent a profit loss from those attacks, the industry has sought insurance coverage. The difficulty arises within these insurance policies as to the definition of “piracy,” and whether acts that more closely resemble terroristic activities as opposed to the traditional notion of piracy are covered. This Student Note evaluates the evolving definition of piracy, both within the United States’ court system and in international law. The lack of a consistent definition raises the argument that policy coverage varies too significantly to effectively protect the economic loss associated with a pirate attack. The Note concludes by noting that regardless of how piracy is defined, the threat of attacks still exists. Additionally, due to liability under the United Nations Convention for the International Sale of Goods (CISG), insurance coverage within the shipping industry will still be sought. <!–EndFragment–>